Nafion-H® catalyzed efficient condensation of indoles with aromatic aldehydes in PEG-water solvent system: A green approach - Mazaahir Kidwai; Ritika Chauhan; Divya Bhatnagar (Arabian Journal of Chemistry, 2016)
Nafion-H® has been used as an efficient and reusable catalyst for an improved and rapid synthesis of bis(indolyl)methanes from electrophilic substitution of indoles with aromatic aldehydes using PEG-400:water system as medium. This methodology offered remarkable improvements in the synthesis of bis(indolyl)methanes with regard to the yield of the products, operational simplicity and green aspects by avoiding the use of expensive, toxic catalysts and solvents. Also the catalyst could be recovered after the completion of reaction and reused several times without any significant loss in its catalytic potential.